Successful Second Microsurgical Replantation for Amputated Penis. Issue 9 (September 2017) - Fujiki, Masahide; Ozaki, Mine; Kai, Akiko; Takushima, Akihiko; Harii, Kiyonori
Abstract : Summary: Penile amputation is a rare emergency, but the best method for its repair is required due to the organ's functional and societal role. Since the first successful microsurgical replantation of the amputated penis, microsurgical techniques have matured and become the standard treatment for the penile replantation. However, the successful second microsurgical replantation for amputated penis has been rarely reported. We present the case of a 40-year-old man with schizophrenia who had a past history of penile self-mutilation and successful replantation at another hospital 2 years ago. After stopping oral medication for schizophrenia, he again cut his penis with a kitchen knife. We successfully replanted the amputated penis by anastomosing both circumflex arteries, the superficial dorsal vein, and the deep dorsal vein using microsurgical techniques. Postoperatively, the foreskin of the replanted penis gradually developed partial necrosis, requiring surgical debridement. The aesthetic and functional results were satisfactory and retrograde urethrography showed no evidence of leakage and stricture of the urethra. Although skin necrosis after penile replantation has been reported as an unavoidable process owing to the nature of injury, the rate would be higher after secondary replantation because of scar formation due to the previous operation. Therefore, our case of successful secondary replantation suggests that skin necrosis would be a predictable postoperative complication and the debridement timing of the devitalized foreskin should be closely monitored, and also secondary amputation is not a contraindication of replantation.